Dielectric anomalies and interactions in the three-dimensional quadratic band touching Luttinger semimetal Pr2Ir2O7 - Bing Cheng (Nature Portfolio, 2017)
The electronic structure of Pr2Ir2O7 contains a quadratic band touching, which is expected to lead to unusual interaction-driven behavior. Here, the authors use spectroscopic measurements to observe signatures of strong interactions but also that Fermi liquid behavior is retained at low temperatures.